2012
DOI: 10.1534/genetics.112.139469
|View full text |Cite
|
Sign up to set email alerts
|

A Non-Mendelian MAPK-Generated Hereditary Unit Controlled by a Second MAPK Pathway inPodospora anserina

Abstract: The Podospora anserina PaMpk1 MAP kinase (MAPK) signaling pathway can generate a cytoplasmic and infectious element resembling prions. When present in the cells, this C element causes the crippled growth (CG) cell degeneration. CG results from the inappropriate autocatalytic activation of the PaMpk1 MAPK pathway during growth, whereas this cascade normally signals stationary phase. Little is known about the control of such prion-like hereditary units involved in regulatory inheritance. Here, we show that anoth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
62
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 41 publications
(72 citation statements)
references
References 41 publications
10
62
0
Order By: Relevance
“…Conversely, perithecia will arrest at a precise stage if the gene is required at this stage in the zygotic tissues. We have used this method to analyze the PaMpk1, PaMpk2, PaNox1, PaNoxR, IDC1 mutants [14,18,19] confirming and completing previous data: PaMpk1, PaMpk2 are required only in the mycelium, PaNox1 and PaNoxR only in the maternal tissues of the fruiting bodies and IDC1 both in the mycelium and in the maternal tissues. We have also analyzed the pah5 beak defect [8] and showed that it was indeed due to a problem in the maternal tissues, as expected since the beak is made from maternal cells and not zygotic ones.…”
Section: Mosaic Analysis With the Mat Mutantsupporting
confidence: 83%
See 2 more Smart Citations
“…Conversely, perithecia will arrest at a precise stage if the gene is required at this stage in the zygotic tissues. We have used this method to analyze the PaMpk1, PaMpk2, PaNox1, PaNoxR, IDC1 mutants [14,18,19] confirming and completing previous data: PaMpk1, PaMpk2 are required only in the mycelium, PaNox1 and PaNoxR only in the maternal tissues of the fruiting bodies and IDC1 both in the mycelium and in the maternal tissues. We have also analyzed the pah5 beak defect [8] and showed that it was indeed due to a problem in the maternal tissues, as expected since the beak is made from maternal cells and not zygotic ones.…”
Section: Mosaic Analysis With the Mat Mutantsupporting
confidence: 83%
“…Note that recovery of high numbers of mosaic perithecia would indicate a non-autonomous action of the mutated gene, i.e., only a fraction of the cells from the fruiting bodies being wild-type would be sufficient to promote normal development, possibly because the product of the wild-type gene would diffuse in the whole fruiting body. We have used this method to analyze mutants of the PaNox1, PaNoxR, PaMpk1, PaMpk2 and IDC1 genes [14,16,18,19]. The results confirmed and completed those of the grafting analysis: PaMpk1 and PaMpk2 are not required in the perithecium, but only in the mycelium; PaNox1 and PaNoxR are required only in the fruiting body and IDC1 is required in both the mycelium and the fruiting body.…”
Section: Fig (3) Grafting With Mutantssupporting
confidence: 58%
See 1 more Smart Citation
“…Genetic analysis has shown that the production of the P. anserina appressorium-like structures is under the control of signalling pathways, which include the PaMpk2/PaMKK2/PaTLK2 MAP kinase module, as well as the PaNox1 and PaNox2 NADPH oxidase enzymes and their regulatory subunits, PaNoxD/PaNoxR and PaPls1/PaNoxR, respectively (Brun et al, 2009;Lalucque et al, 2012;Lacaze et al, 2015). However, it does not depend on the PaMpk1 or PaMpk3 pathways or the PaNox3 NADPH oxidase (Brun et al, 2009;Lalucque et al, 2012).…”
Section: Biomass Colonization Mechanismsmentioning
confidence: 99%
“…However, it does not depend on the PaMpk1 or PaMpk3 pathways or the PaNox3 NADPH oxidase (Brun et al, 2009;Lalucque et al, 2012). The PaNox2 complex and the PaMpk2 MAP kinase are important for the initial reorientation phase, while the PaNox1 complex is involved in the generation of the needle-like hyphae.…”
Section: Biomass Colonization Mechanismsmentioning
confidence: 99%